EXPLORATION OF ETHNOMATHEMATICS IN BENGKULU AS A SOURCE OF MATHEMATICS LEARNING FOR ELEMENTARY SCHOOL STUDENTS - Agusdianita, Neza; Yusnia; Dwi Shofiya Magfira Izzania, Rizqa; Lorenza, Sovia (ATTA`DIB, 2025)
The Merdeka Curriculum implements a multicultural approach in learning. Therefore, ethnomathematics is needed in elementary school mathematics learning. The purpose of this study is to explore the ethnomathematics found in Bengkulu and integrate it into the mathematics curriculum as a learning resource for first-grade elementary school students. This qualitative research with an ethnographic approach was conducted over a period of one year. The research activities include: (1) Identifying the ethnomathematics found in Bengkulu, (2) Mapping the learning achievements and indicators of the mathematics subject in the Merdeka Curriculum for first-grade elementary school, (3) Analyzing the ethnomathematics of Bengkulu City that can be integrated into the learning achievements and indicators of the mathematics subject in the Merdeka Curriculum for first-grade elementary school, and (4) Developing a draft of recommended mathematics teaching materials based on Bengkulu ethnomathematics. The research results obtained are (1) data on Bengkulu ethnomathematics, (2) mapping of learning achievements and indicators of the mathematics subject in the Merdeka Curriculum for first-grade elementary school, and (3) a product of mathematics teaching materials based on the ethnomathematics of Bengkulu City.